DEVELOPING ENGLISH LESSON PLANS FOR THE FIRST YEAR STUDENTS OF SMA 18 MAKASSAR BASED ON THE 2013 CURRICULUM - Djuwairiah Ahmad; Husnul Khatimah Nur (ETERNAL (English, Teaching, Learning and Research Journal), 2015)
This research developed English lesson plan based on 2013 curriculum for the first year students of SMAN 18 Makassar. The objective of this research was to develop English lesson plans based on the 2013 curriculum. It was conducted at the first year students of SMAN 18 Makassar. The significance of this research was for students and teacher. For students, the product of this research made the students more active in the teaching learning process. Then, for the teacher was helped them to make or design good lesson plans based on the 2013 curriculum. The research design of this research was Research & Development (R&D). It applied model R&D which adapted from Borg & Gall model. The steps of the model were research and information collecting, planning, developing preliminary form of product, main product revision, final product revision, and dissemination and implementation. The types of data of this research were qualitative and quantitative data. The research instruments were expert validation sheet and teacher feedback sheet to obtain the data about the product. The result of the research showed that the product was valid to implement in the classroom. It can be seen that the product valid from score that expert and teacher gave. The validation score that the researcher got was 80% meant the product was very good and score from teacher feedback was 95%. Based on the data above, the researcher concluded that developing English lesson plans based on 2013 curriculum that the researcher conducted was very good with the score on 80%-95%.